Urgent catheter ablation for sustained ventricular tachyarrhythmias in patients with acute heart failure decompensation. Issue 1 (14th July 2013) - Hayashi, Meiso; Miyauchi, Yasushi; Murata, Hiroshige; Takahashi, Kenta; Tsuboi, Ippei; Uetake, Shunsuke; Hayashi, Hiroshi; Horie, Tsutomu; Yodogawa, Kenji; Iwasaki, Yu-ki; Mizuno, Kyoichi
Abstract: Aims: Ventricular tachycardia (VT) and ventricular fibrillation (VF) are not uncommon in patients hospitalized with acute heart failure (AHF). We sought to evaluate the efficacy of urgent radiofrequency catheter ablation (RFCA) for recurrent VT/VF during AHF decompensations. Methods and results: The present study retrospectively analysed the data of 15 consecutive patients (69 ± 9 years, ischaemic heart disease in 10), who underwent urgent RFCA for frequent drug-refractory VT/VF episodes during an AHF decompensation with pulmonary congestion. The target arrhythmias were clinically documented monomorphic VTs in 10 patients, frequent premature ventricular contractions (PVCs) triggering VF in 4, and both in 1. The mean left ventricular ejection fraction was 26 ± 8%. The maximum number of arrhythmia episodes over 24 h was 9.1 ± 11.7. All RFCA sessions were completed without any major complications except for a temporary deterioration of pulmonary congestion in three patients (20%). Elimination and non-inducibility of the target arrhythmias were achieved in 13 patients (87%). Successful ablation site electrograms showed Purkinje potentials for all 5 PVCs triggering VF and 4 of 14 clinically documented monomorphic VTs (29%). Five patients (33%) underwent second sessions 10 ± 4 days after the first session for acute recurrences. Sustained VT/VF was completely suppressed during admission in 12 patients (80%), and the AHF ameliorated in 13 patients (93%). Twelve patients (80%) were discharged alive. Conclusion: Urgent RFCA for drug-resistant sustained ventricular tachyarrhythmias during AHF decompensations would be an appropriate therapeutic option. Purkinje fibres can be ablation targets not only in those with PVCs triggering VF, but also in those with monomorphic VT.